Analysis of CYS3 regulator function in Neurospora crassa by modification of leucine zipper dimerization specificity. - Paietta, J V (1995)
The CYS3 positive regulator is a basic region-leucine zipper (bZIP) DNA-binding protein that is essential for the expression of sulfur-controlled structural genes in Neurospora crassa. An approach of modifying the dimerization specificity of the CYS3 leucine zipper was used to determine whether the in vivo regulatory function of CYS3 requires the formation of homodimeric or heterodimeric complexes. Two altered versions of CYS3 with coiled coil elecrostatic interactions favorable to heterodimerization showed restoration of wild-type CYS3 function only when simultaneously expressed in a delta cys-3 strain. In addition, constructs having the CYS3 leucine zipper swapped for that of the oncoprotein Jun or the CYS3 leucine zipper extended by a heptad repeat showed wild-type CYS3 function when transformed into a delta cys-3 strain. Gel mobility shift and immunoprecipitation assays were used to confirm the modified CYS3 proteins dimerization and DNA binding properties. The studies, which precluded wild-type CYS3 dimerization, indicate that in vivo CYS3 is fully functional as a homodimer since no interaction was required with other leucine zipper proteins to activate sulfur regulatory and structural gene expression. The results demonstrate the utility of leucine zipper modification to study the in vivo function of bZIP proteins.